The expatriates : a novel - Lee, Janice Y. K. (Viking, 2016)
"The New York Times bestselling author of The Piano Teacher returns with a transporting novel about motherhood, marriage, and the elusive nature of happiness, focusing on the lives of three very different American women living in Hong Kong. In her stunning follow-up to her acclaimed first novel, Janice Lee explores the emotions, identities, and relationships of three American women living in the same small expat community in Hong Kong. Mercy, a young Korean-American and a recent Columbia graduate without a safety net, is adrift, undone by a terrible incident in her recent past. Hilary, a lonely housewife, is haunted by her struggle to have a child, something she believes could save her foundering marriage. Meanwhile, Margaret, once a happily married mother of three, takes every opportunity to escape from her life in the wake of a shattering loss. As each woman struggles with her own demons, their lives collide in ways that have irreversible consequences for them all. Atmospheric, moving, and utterly compelling, The Expatriates confirms Lee as an exceptional talent and one of our keenest observers of women's inner lives"--